Decolourization of recovered base oil from used lubricant oil: a study on the performance of composite adsorbents - Hishamuddin, Elina; Foo, Chwan Yee; Mohd Yunus, Rosli; Lim, Lee Ping; Ripin, Adnan (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The process of decolourizing used oil is usually done by adsorption to remove the darkish colour and lighten the oil for further purification [1]. This paper discusses the results of a study carried out to determine the performance of composite adsorbents comprising a mixture of activated carbon and activated clay in decolourizing recovered base oil. The recovered base oil is contacted with a certain percentage of the chosen adsorbents where the colour of this oil is compared to new virgin oil by using a spectrophotometer. Based on the results from the factorial design analysis, an adsorbent mixture of 12 grams containing 80% activated clay and 20% activated carbon added to 100 ml of base oil at 60Â°C produced the best decolourized base oil. Besides that, from four parameters studied in this case, which are the ratio of adsorbents, operating temperature, the ratio of adsorbents/oil and number of contact stages, the most influential parameter affecting the adsorption process was the ratio of adsorbents added to the base oil while the interaction between the operating temperature and the number of contact stages was the most significant of all interactions under study.